Virtualised EAST-WEST PON Architecture Supporting Low-Latency communication for Mobile Functional-Split Based on Multi-Access Edge Computing - Ruffini, Marco; Anandarajah, Aleksandra (My University, 2020)
Ultralow latency end-to-end communication with high reliability is one of the most important requirements in 5G networks to support latency-critical applications. A recent approach toward this target is to deploy edge computing nodes with networking capabilities, known as multiaccess edge computing (MEC), which can greatly reduce the service end-to-end latency. However, the use of MEC nodes poses radical changes to the access network architecture. This requires movement from the classical point-to-multipoint (or point-to-point) structure, used to deliver residential broadband and cloud radio access network (Cloud-RAN) services, to a mesh architecture that can fully embed the MEC nodes with all other end points (i.e., mobile cells, fixed residential, businesses). In this paper, we propose what we believe to be a novel passive optical network (PON)-based mobile fronthaul transport architecture based on PON virtualization that allows EAST–WEST communication along with traditional NORTH–SOUTH communication. The architecture enables the end points of a PON tree, where usually optical networking units (ONUs) are located, to also host MEC nodes by deploying an edge optical line terminal (OLT) capable of communicating directly with adjacent ONUs, by reflecting wavelength signals from the splitter nodes. We experimentally show that signal backscattering due to the reflection at the splitter does not affect the system performance. In addition, using protocol level simulations, we show how this architecture can maintain low latency (≈100µs≈100µs) in varying mobile traffic conditions by offloading ONUs (i.e., where remote units of Cloud-RAN cells are located) to other edge OLTs through dynamic formation of virtual PON slices. Furthermore, our results show how an efficient migration strategy for ONUs can be chosen depending on the traffic load, different functional split configurations, and the PON capacity.
PUBLISHED
Keywords: Ultralow latency; 5G networks; Multiaccess Edge Computing (MEC); Access network architecture; Passive Optical Network (PON); Cloud Radio Access Network (Cloud-RAN); Optical Line Terminal (OLT); Optical Networking Units (ONUs)